Analysis Of The Relationship Between Concentration And Balance Against Yoep Chagi Kick Poomsae Movement Technique Sports Club Taekwondo Achievement State University Of Jakarta - Fahmy Fachrezzy; Uzizatun Maslikah; Masnur Ali; Iwan Hermawan; Reggie Reginald; Haris Nugroho (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to analyze the relationship of Concentration and Balance with yeop chagi kicks  Achievement Sports Club taekwondo  State University of Jakarta.   The population and sample in the study were college students who attended a sports club achievement of 35 men with exercise characteristics for a year or more. Data collection techniques use tests and measurements of concentration, balance, and yeop chagi kicks. Technical data analysis uses a significant multiple-level correlation ? 0.05 overall data analysis using    SPSS software version 20. The results of this study can conclude that: (i) there is a relationship between concentration and yeop chagi kick poomsae movement technique; (ii) there is a relationship between concentration and yeop chagi kick Poomsae movement technique; and (iii) there is a relationship between Concentration and Balance with yeop chagi kick poomsae movement technique.  But in this study only involved one factor of physical condition and psychology, for further research will involve other physical condition factors namely speed, flexibility, endurance, and related in this study by the characteristics of taekwondo achievement, especially in poomsae numbers at the State University of Jakarta.